2016
DOI: 10.1259/bjr.20150704
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement of multicompartment ultrasound in the assessment of pelvic floor anatomy

Abstract: Objective: To assess the interobserver agreement of pelvic floor anatomical measurements using multicompartment pelvic floor ultrasound. Methods: Females were recruited from the urogynaecology/gynaecology clinics between July and October 2009 and underwent multicompartment pelvic floor ultrasonography (PFUS) using twodimensional (2D) transperineal ultrasound (TPUS), high-frequency 2D/three-dimensional (3D) endovaginal ultrasound (EVUS) using a biplane probe with linear and transverse arrays and a 360°rotationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
(68 reference statements)
4
14
0
Order By: Relevance
“…showed excellent agreement for diagnosis of anismus on 2D‐TPUS as compared with anal and vaginal ultrasound, but diagnostic test characteristics were not calculated due to lack of a reference standard for anismus. Interobserver agreements of rectocele depth measurement on 2D‐TPUS and diagnosis of rectocele, enterocele and intussusception on 4D‐TPUS were similar to those in other studies. Dietz et al .…”
Section: Discussionsupporting
confidence: 78%
“…showed excellent agreement for diagnosis of anismus on 2D‐TPUS as compared with anal and vaginal ultrasound, but diagnostic test characteristics were not calculated due to lack of a reference standard for anismus. Interobserver agreements of rectocele depth measurement on 2D‐TPUS and diagnosis of rectocele, enterocele and intussusception on 4D‐TPUS were similar to those in other studies. Dietz et al .…”
Section: Discussionsupporting
confidence: 78%
“…The mean urethral length assessed by a foley catheter was found to resemble that assessed using 3D transperineal ultrasound (3.02 ± 0.41 cm and 3.03 ± 0.34 cm, respectively), suggesting agreement between the two methods. This data is also in line with previous studies reporting a urethral length range of 2‐4 cm measured with introital ultrasound in women with SUI . Also supporting the agreement between the two methods, the ICC obtained suggests excellent accordance (ICC = 0.90) with the standard proposed by Portney et al Moreover, the Bland‐Altman analysis revealed a mean difference close to 0 (−0.01 ± 0.23 cm), showing little to no bias between the two methods.…”
Section: Discussionsupporting
confidence: 91%
“…This data is also in line with previous studies reporting a urethral length range of 2-4 cm measured with introital ultrasound in women with SUI. 16,17,23 Also supporting the agreement between the two methods, the ICC obtained suggests excellent accordance (ICC = 0.90) with the standard proposed by Portney et al 20 Moreover, the Bland-Altman analysis revealed a mean difference close to 0 (−0.01 ± 0.23 cm), showing little to no bias between the two methods. Limits of agreement (−0.45 cm and 0.46 cm) provide a clinically acceptable range in which a minimum of 95% of the values should be expected, given the concordance between methods.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations